The freshwater mollusks (Gastropoda, Pulmonata, Lymnaeidae) from the Lower Sarmatian for Ukraine and Poland - Kovalenko, V.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
The species distribution data for the lower Sarmatian freshwater mollusks (Gastropoda, Pulmonata, Lymnaeidae) of the southern Ukraine (Zbruch strata), Volyn-Podolia (the Western Ukraine), and the Central Poland (Kuzhorsky strata) are generalized. The new subspecies of Lymnaea s. str – Lymnaea (Lymnaea) stagnalis turgidiformis K o v a l e n k o subsp. nov section of Lymnaea s. str subgenus has been described.